The Effectiveness of Skimming and Scanning Techniques in Improving Student’s Reading Comprehension of Grade Eleven Students of SMA Negeri 1 Tana Toraja - Yanti Mambua (Journal of Social Science, 2020)
This research aims at proving that the use of using Skimming and Scanning techniques are effective in improving reading comprehension of grade-eleven students of SMA Negeri 1 Tana Toraja. The method used in this research was true-experimental design random assignment pretest-posttest control group. The samples of this research were selected from the population of grade-eleven students of SMA Negeri 1 Tana Toraja by using random sampling technique. The instruments of data collection were observation checklist, questionnaire items and tests. The data were analyzed by using t-test statistical and descriptive methods. Based on the analysis, the result score of experimental class is 80.27 and control class is 67.02. By applying level of significance 0.05 and degree of freedom (df) 48, the t-counted value (4.3) is greater than t-table value (2013). Furthermore, based on the result of effectiveness indicators showed the score is 83% it means that the techniques are effective. In other words, applying skimming and scanning techniques are effective in improving students reading comprehension of the grade eleven students of SMA Negeri 1 Tana Toraja. Keywords: Reading Comprehension Skimming and Scanning